Necrotizing Liver Granuloma/Abscess and Constrictive Aspergillosis Pericarditis with Central Nervous System Involvement: Different Remarkable Phenotypes in Different Chronic Granulomatous Disease Genotypes - Sanem Eren Akarcan; Neslihan Karaca; Guzide Aksu; Halil Bozkaya; Mehmet Fatih Ayik; Yasemin Ozdemir Sahan; Mehmet Arda Kilinc; Zafer Dokumcu; Cenk Eraslan; Emre Divarci; Hudaver Alper; Necil Kutukculer (Case Reports in Immunology, 2017)
Chronic granulomatous disease (CGD) is a primary immune deficiency causing predisposition to infections with specific microorganisms, Aspergillus species and Staphylococcus aureus being the most common ones. A 16-year-old boy with a mutation in CYBB gene coding gp91phox protein (X-linked disease) developed a liver abscess due to Staphylococcus aureus. In addition to medical therapy, surgical treatment was necessary for the management of the disease. A 30-month-old girl with an autosomal recessive form of chronic granulomatous disease (CYBA gene mutation affecting p22phox protein) had invasive aspergillosis causing pericarditis, pulmonary abscess, and central nervous system involvement. The devastating course of disease regardless of the mutation emphasizes the importance of early diagnosis and intervention of hematopoietic stem cell transplantation as soon as possible in children with CGD.